Beyond The Classroom: At War With the Buddha of Love - (:unkn) unknown (Kansas State University. K-State First., 2015)
A poster promoting the presentation "At War With the Buddha of Love," hosted by Dr. Jessica Falcone, Associate Professor of Anthropology, at Kansas State University on April 28, 2015 at 7 PM.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Buddha; Posters